2014
DOI: 10.1073/pnas.1316342111
|View full text |Cite
|
Sign up to set email alerts
|

Synergies between climate and management for Atlantic cod fisheries at high latitudes

Abstract: The widespread depletion of commercially exploited marine living resources is often seen as a general failure of management and results in criticism of contemporary management procedures. When populations show dramatic and positive changes in population size, this invariably leads to questions about whether favorable climatic conditions or good management (or both) were responsible. The Barents Sea cod (Gadus morhua) stock has recently increased markedly and the spawning stock biomass is now at an unprecedente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
192
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(196 citation statements)
references
References 54 publications
4
192
0
Order By: Relevance
“…The time series was characterized by a prolonged period of high exploitation from the 1970s to early 1990s, resulting in an increasing proportion of stocks falling to biomass levels below precautionary levels (25). A declining trend in exploitation has been evident since the early 2000s and, combined with the near abolishment of illegal, unreported, and unregulated fishing, some cod stocks have been showing signs of major improvement (26). On the other hand, a recent study (27) suggested that the trends in abundance and distribution of Northeast Arctic cod (stock 22) (Fig.…”
Section: Significancementioning
confidence: 99%
“…The time series was characterized by a prolonged period of high exploitation from the 1970s to early 1990s, resulting in an increasing proportion of stocks falling to biomass levels below precautionary levels (25). A declining trend in exploitation has been evident since the early 2000s and, combined with the near abolishment of illegal, unreported, and unregulated fishing, some cod stocks have been showing signs of major improvement (26). On the other hand, a recent study (27) suggested that the trends in abundance and distribution of Northeast Arctic cod (stock 22) (Fig.…”
Section: Significancementioning
confidence: 99%
“…Moreover, a proper assessment of the impacts of declines and losses is impossible without considering the effect of gains. For instance, declines of cod stocks in the Scotian Shelf have led to shrimp and crab fisheries exceeding by value that of the cod fishery it replaced (Frank et al, 2005) while poleward expansion of cod habitat into the Arctic with climate change has led to enhanced arctic cod fishery with warming (Kjesbu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas much attention has been devoted to the threats to key species, such as Calanus copepods (Wassmann, 2011), or charismatic species, such as the polar bear (Renaud et al, 2008;Wassmann, 2011), with arctic climate change, very little attention has been given to ecological significance of new species entering the Arctic and the expansion of existing arctic species. For instance, the cod stock in the Barents Sea has reached a historical maximum partially due to expansion of their suitable habitat with climate change, with this increase in cod stock catalyzed further by a sound management program (Kjesbu et al, 2014). This example shows how forecasts of future key species, habitats, and ecosystems in the Arctic with climate change might inform management and policy strategies to maximize the delivery of ecosystem services to society in the face of climate change.…”
Section: Introductionmentioning
confidence: 99%
“…Currently the Barents Sea cod (Gadus morhua) stock is record high, as a result of successful fisheries management and favorable climate conditions, making it the world's largest cod fishery [37]. The pelagic fishery…”
Section: Barents Sea and Central Arctic Oceanmentioning
confidence: 99%